2020
DOI: 10.1063/1.5139044
|View full text |Cite
|
Sign up to set email alerts
|

Frenkel–Holstein Hamiltonian applied to absorption spectra of quaterthiophene-based 2D hybrid organic–inorganic perovskites

Abstract: For the prototypical two-dimensional hybrid organic–inorganic perovskites (2D HOIPs) (AE4T)PbX4 (X = Cl, Br, and I), we demonstrate that the Frenkel–Holstein Hamiltonian (FHH) can be applied to describe the absorption spectrum arising from the organic component. We first model the spectra using only the four nearest neighbor couplings between translationally inequivalent molecules in the organic herringbone lattice as fitting parameters in the FHH. We next use linear-response time-dependent density functional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 108 publications
0
19
0
Order By: Relevance
“…In Ref. 311, the interactions between the organic and inorganic excitons in AE4TPbX 4 was assumed to be negligible. Despite this approximation, the theoretical study reported in Ref.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Ref. 311, the interactions between the organic and inorganic excitons in AE4TPbX 4 was assumed to be negligible. Despite this approximation, the theoretical study reported in Ref.…”
Section: Discussionmentioning
confidence: 99%
“…7 show that simulations using the MHF reproduce the vibronic progression arising from the organic component in (AE4T)PbX 4 (X = Cl, Br, and I). 311 It was also found that the choice of the halide ion in the inorganic component plays a central role in determining the shape of the vibronic structure observed in oligothiophene based perovskites. 311 The transition spacings in the excitonic spectra seem to directly correlate with the choice of the organic spacer.…”
Section: Excitons In Hybrid Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…In analogy to the classical decomposition of the electronic density into point charges localized on the atoms’ nuclear centers, we can decompose the electronic transition density into atomic transition charges centered on the atomic centers (tqs). ,, Hence, eq becomes N K and N L are the number of atoms in each chromophore, and R I , R J are the nuclear coordinates. Mulliken population analysis has been used extensively to derive the atomic transition charges from the electronic transition density matrix between ground and excited singlet state the same way we would use it to derive the classical partial charges from the electronic density matrix of a single state. ,, In the Mulliken-based treatment, we use the transition density matrix between the ground and an excited state to calculate the atomic transition charges in a similar way as it is done for the electron density of an individual electronic state. , In this approach, electrons associated with basis functions centered on a given atom are used in calculating the partial charge of that atom, while electrons “shared” between basis functions centered on different atoms are divided evenly between the two atoms.…”
Section: Methodsmentioning
confidence: 99%
“…For the system-bath interaction, we consider the archetypical spin-boson and displaced harmonic oscillator (or Frenkel-Holstein) models as they have been found to be useful to describe a variety of problems. This includes quantum impurity problems, [52] quantum thermodynamics [53], artificial light-matter coupling [54] for the spin-boson coupling, and molecular photophysics such as the dynamics of natural [55] and artificial chromophore aggregates, [56] photo-voltaic materials, [57] and electro-luminescent materials [58] for the displaced harmonic oscillator.…”
Section: A Target Hamiltonianmentioning
confidence: 99%